National community, myth or reality: collaboration of ordinary Germans with the Nazi regime - Vuković, Slobodan (Napredak, 2022)
The national community (Volksgemeinschaft) is one of the central concepts of Nazi ideology and propaganda. At the beginning of the Great War, it served to strengthen national unity regardless of religion or social status in the upcoming struggle for living space (Lebensraum). The Völkisch movement and Nazism emphasize the racial worldview, anti-Semitism and anti-Slavism in the national community. It constitutes the unity of the "race", the Volk and the new German “religion”. It was raised as a concept of separation into national comrades and foreigners outside the community. Jews, Slavs, political opponents and the mentally or physically handicapped were excluded from the national community. Mass crimes were committed against them and finally the research shows that Nazism had the broad support of the German Volk.